RESTRUKTURISASI PEMBIAYAAN MURABAHAH DALAM MENDUKUNG MANAJEMEN RISIKO SEBAGAI IMPLEMENTASI PRUDENTIAL PRINCIPLE PADA BANK SYARIAH DI INDONESIA - Faisal, Faisal (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Murabahah finance to syariah bank was restructured by rescheduling, reconditioning, and prudential principle. It means that syariah bank had considered various aspects, such as, minimizing syariah bank risk and not making customers disadvantageous, even making both parties advantageous, in the restructuring. Then, the syariah bank must also consider basic Islamic economic principles, such as, riba, gharar and maisir as carefulness in Islamic law. Furthermore, applications of customer service principles, such as, know your customer principles, syariah principle and syariah accounting principle are an inherent part which cannot be separated from prudential principle. Application of the principles is syariah bank loyalty to valid regulation in restructuring finance.Key words: restructuring, murabahah, prudential principle